Metal-Insulator Transition of Solid Hydrogen by the Antisymmetric Shadow Wave Function - Calcavecchia, Francesco; Kühne, Thomas D. (Zeitschrift für Naturforschung Section A - A Journal of Physical Sciences, 2018)
We revisit the pressure-induced molecular-Atomic metal-insulator transition of solid hydrogen by means of variational quantum Monte Carlo simulations based on the antisymmetric shadow wave function. For the purpose of facilitating the study of the electronic structure of large-scale fermionic systems, the shadow wave function formalism is extended by a series of technical advancements as implemented in our HswfQMC code. Among others, these improvements include a revised optimization method for the employed shadow wave function and an enhanced treatment of periodic systems with long-range interactions. It is found that the superior accuracy of the antisymmetric shadow wave function results in a significantly increased transition pressure with respect to previous theoretical estimates.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Fermion Sign Problem; Metallic Hydrogen; Quantum Monte Carlo; Shadow Wave Function.